Press Non-Compliance in Presenting Digital Literacy Information in the Era of Civil Society: A Normative Juridical Study in Indonesia (2023–2025) - Donny Irawan; Ahmad Heru Romadhon; Dhofirul Yahya; Rahayu Sri Utami (CV. RADJA PUBLIKA, 2026)
The rapid expansion of digital journalism in Indonesia has generated significant challenges regarding legal compliance, journalistic ethics, and the quality of information disseminated to the public. Despite the growing importance of digital literacy in strengthening democratic participation and civil society, studies examining press non-compliance from an integrated legal and socio-legal perspective remain limited. This study aims to analyze the forms of press non-compliance in presenting digital literacy-related information and to examine the effectiveness of legal enforcement mechanisms governing digital journalism in Indonesia during the period 2023–2025. Employing a qualitative normative-juridical approach with a socio-legal perspective, the research utilizes document analysis of statutory regulations, the Journalistic Code of Ethics, Press Council decisions, legal documents, and selected cases of digital news reporting. The findings reveal four dominant forms of non-compliance: inadequate verification of information, sensationalist and clickbait-oriented reporting, violations of privacy and personal dignity, and politically biased news framing. The study further demonstrates that existing enforcement mechanisms remain fragmented due to overlapping institutional authorities, limited monitoring capacity, and the predominantly administrative nature of sanctions imposed by regulatory bodies. These conditions contribute to weak accountability and reduce the deterrent effect of legal regulation in the digital media environment. The research also shows that persistent press non-compliance negatively affects public digital literacy by increasing vulnerability to misinformation, weakening public trust in media institutions, and undermining the deliberative function of civil society. This study contributes to socio-legal scholarship by integrating press law, media ethics, and digital literacy within a civil society framework and argues that press freedom in the digital era must be understood as freedom accompanied by legal responsibility and ethical accountability. Strengthening institutional oversight, professional ethics, and public digital literacy is therefore essential for sustaining democratic communication in Indonesia.